The Effectiveness of the Family of Hope Program (PKH) in Lamu Village, Batudaa Pantai District, Gorontalo District - Erlina Husain; Widya Kurniati Mohi; Lukfiah Irwan Radjak (Journal of Management and Administration Provision, 2021)
The purpose of this study was to determine the effectiveness of the Family Hope Program (PKH) in Lamu Village, Batudaa Pantai District, Gorontalo Regency. The method used in this study was qualitative. The results showed that the effectiveness of the Family Hope Program in Lamu Village by using four indicators of program effectiveness, namely the accuracy of program targets, program socialization, program objectives, and program monitoring. There are two indicators that are fulfilled, namely program socialization and program monitoring. This is evident from the activeness of PKH facilitators in conducting program socialization and monitoring both directly and indirectly. Two other indicators that have not yet been achieved are the accuracy of the targets and objectives of the program because there are still some residents who are able to participate in receiving PKH assistance and the utilization of aid funds is still not in line with the objectives expected by the government.